Estimation of extremely small field radiation dose for brain stereotactic radiotherapy using the Vero4DRT system. (June 2018) - Nakayama, Shinichi; Monzen, Hajime; Onishi, Yuichi; Kaneshige, Soichiro; Kanno, Ikuo
Highlights: A dosimetric validation of the Vero4DRT for brain SRT with extremely small fields. Dose verification was performed for the brain SRT plans by using chamber and films. Accurate radiation doses delivery for small field larger than or equal 10 × 10 mm 2 . Abstract: The purpose of this study was a dosimetric validation of the Vero4DRT for brain stereotactic radiotherapy (SRT) with extremely small fields calculated by the treatment planning system (TPS) iPlan (Ver.4.5.1; algorithm XVMC). Measured and calculated data (e.g. percentage depth dose [PDD], dose profile, and point dose) were compared for small square fields of 30 × 30, 20 × 20, 10 × 10 and 5 × 5 mm 2 using ionization chambers of 0.01 or 0.04 cm 3 and a diamond detector. Dose verifications were performed using an ionization chamber and radiochromic film (EBT3; the equivalent field sizes used were 8.2, 8.7, 8.9, 9.5, and 12.9 mm 2 ) for five brain SRT cases irradiated with dynamic conformal arcs. The PDDs and dose profiles for the measured and calculated data were in good agreement for fields larger than or equal to 10 × 10 mm 2 when an appropriate detector was chosen. The dose differences for point doses in fields of 30 × 30, 20 × 20, 10 × 10 and 5 × 5 mm 2 were +0.48%, +0.56%, −0.52%, and +11.2% respectively. In the dose verifications for the brain SRT plans, the mean dose difference between the calculated and measured doses were −0.35% (range, −0.94% to +0.47%), with the average pass rates for the gamma index under the 3%/2 mm criterion being 96.71%, 93.37%, and 97.58% for coronal, sagittal, and axial planes respectively. The Vero4DRT system provides accurate delivery of radiation dose for small fields larger than or equal to 10 × 10 mm 2 .